2014
DOI: 10.1002/mawe.201400286
|View full text |Cite
|
Sign up to set email alerts
|

Superplastic forming ability of as‐cast AZ91 Mg alloy prepared by twin roll casting

Abstract: In this study, the twin roll casting process has been utilized to prepare initial as-cast strip of AZ91 alloy that has been further tested in uniaxial tension at 325, 350 and 375°C, and at strain rates from 10 -2 to 10 -4 s -1 . The ability of AZ91 strip to undergo superplastic or superplastic-like deformation in longitudinal direction, in transverse direction, and in 45 degrees to longitudinal direction was investigated with no further thermal or thermomechanical processing applied prior to the testing. At te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The most well-known aluminum alloy of this category is for instance the SUPRAL alloy, developed in the seventies [42]. In the same spirit, it has been recently shown that die cast or twin rolled magnesium alloys could also exhibit large ductilities without any specific treatments [43,44]. Another interesting situation is related to possible superplasticity of welded microstructures.…”
Section: Is There a Systematic Benefit To Refine Microstructures?mentioning
confidence: 99%
“…The most well-known aluminum alloy of this category is for instance the SUPRAL alloy, developed in the seventies [42]. In the same spirit, it has been recently shown that die cast or twin rolled magnesium alloys could also exhibit large ductilities without any specific treatments [43,44]. Another interesting situation is related to possible superplasticity of welded microstructures.…”
Section: Is There a Systematic Benefit To Refine Microstructures?mentioning
confidence: 99%